Hubungan Sekolah dan Masyarakat - Idawati; Nurwahidah; Iis Shalihah; Nurul Istiqamah; Nurhidayah (STKIP Subang, 2025)
The urgency of this research stems from the gap in the relationship between schools and communities, which has resulted in low parental participation due to ineffective communication between schools and communities. This study aims to explain the objectives and benefits of school-community relations, as well as to outline the principles and strategies for building good relations between schools and communities. The type of data used is secondary data. The method used in this study is a literature review. The data obtained is compiled, analyzed, and concluded to obtain data related to the literature review. The results of the literature study show that the purpose of the relationship between schools and the community must reflect two-way communication between schools and the community in order to reach a mutual agreement on policies, program planning, and strategies for implementing education in schools. A good relationship between schools and the community is beneficial for improving the quality of learning and facilities, increasing accountability, strengthening social support and resources, creating a conducive environment, and increasing a sense of ownership and responsibility towards the school. The principles of school-community relations include openness, participation, sustainability, authority, sensitivity, and simplicity. Strategies for building harmonious relations between schools and communities include implementing two-way communication by holding meetings to.